The Use of English Short Animation Movies to Improve Students’ Listening Skill: A Study at The First Grade of SMPN 1 Lingsar Academic Year 2022/2023 - Putri Yunita; Arafiq Arafiq; Atri Dewi Azis; Sahuddin Sahuddin (Jurnal Ilmiah Profesi Pendidikan, 2023)
This research aims to find out the effectiveness of using English Short Animation Movies to improve students listening skills at SMPN 1 Lingsar academic year 2022/2023. This research uses quantitative method with an experimental design. The design of the research is quasi experimental research with nont-equivalent control group design two group Experimental group and control group. The population and sample of this research are all first-grade students at SMPN 1 Lingsar.The sample was selected based cluster random sampling technique. The data analysed by using Microsoft Excel and the SPSS program. After analyzing the data, the results were compared between t-test and t-table value of the Experimental and Control groups.,in the experimental group the t-test value is 5.562. The table above shows that t-test value in the experimental group (5.562) is higher than the t-value table (1.67) for alpha 0.05 and (2.66) for alpha 0.01 which means that the result of the experimental t-test are significant. Meanwhile, the results of the t-test from the control group (2.057) in the table above shows that t-test value in the control group ( 2.057)  is lower than the t-table value (1.67) alpha 0.05 and (2.66) for alpha 0.01 which means that the results of the t-test control group are not significant. This means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. So it can be concluded that there is a significant effect in the use of English short animation movie to improve students listening skills at the first grade of SMPN 1 Lingsar.